A highly selective ratiometric fluorescent probe for H2S based on new heterocyclic ring formation and detection in live cells. Issue 5 (4th May 2019) - Samanta, Sandip Kumar; Ali, Syed Samim; Gangopadhyay, Ankita; Maiti, Kalipada; Pramanik, Ajoy Kumar; Guria, Uday Narayan; Ghosh, Aritri; Datta, Pallab; Mahapatra, Ajit Kumar
ABSTRACT: A 3-indolylacrylate derivative, 3-IA, prepared by connecting an ethyl acrylate in 3-position of indole has been synthesised and characterised. Ethyl acrylate moiety acts as the Michael acceptor towards H2 S, and the resultant addition product then participates in intramolecular cyclisation with the ester group at 2-position to form another new heterocyclic ring. Blue fluorescence of3-IA turned into green in presence of H2 S, leading to ratiometric behaviour of the fluorescent sensor with large stokes shift of 55 nm. Probe3-IA has excellent selectivity towards H2 S over other biothiols and other competing anions. Density function theory/time-dependent density function theory calculations were carried out to validate the reaction mechanism and the electronic properties of3-IA . Importantly, the ratiometric probe3-IA shows great promise in H2 S detection by simple visual fluorescent inspection in filter paper-based protocol. The probe shows its excellent ability to detect H2 S in different natural water samples. Furthermore, we have employed our probe to detect H2 S for ratiometric imaging in live Vero cell. Abstract :